Personal hygiene and scabies among students at islamic boarding school in Indonesia - Awisarita Rr. Wiwara; Laariya Tira Alfiani; Prasetyawan Muhammad Farhan; Sulistiyawati; Ulfa Muflihatul; Nisa Afifah Khoiru; Putri Rachma Greta Perdana (BIO Web of Conferences)
Scabies is one of the public health issues that is caused by infestation of Sarcoptes scabiei. Scabies ranked third among the twelve most common skin diseases in Indonesia. The prevalence of scabies is particularly high in boarding school environments. The purpose of this study is to determine the prevalence of scabies in Hamalatul Quran Islamic Boarding School Yogyakarta and to examine its relationship with personal hygiene. In March 2024, a cross-sectional analytical approach was conducted. A total of 123 students were included in this study. Questionnaires were distributed to respondents to gather data on personal hygiene practices. The prevalence of scabies among students in Islamic boarding school was 62.6%. Personal hygiene behavior among the majority of students is predominantly poor. This study showed that there was a relationship between personal hygiene and scabies (p-value = 0.011). Therefore, maintaining personal hygiene is very important to prevent the transmission of scabies.